KARAKTERISTIK PEMUKIMAN KUMUH KOTA BUKITTINGGI (Studi Kasus Kecamatan Aua Tajungkang Tangah Sawah dan Kelurahan Pakan Kurai) - zul haqqi amriza; Yudi Antomi (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determina the characteristics of the slums of the city of Bukittnggi. The method used in this research is the qualitative descriptive method. The results showed the following: 1. Characteristics of the building: a) the state of building there are 2 RTs not conforming to the technical requirements. b) construction density 5 RTs have a high construction density. c) the distance between the building is 1.5 to 2 meters. 2. Characterstics of the installations and infrastrictures: a) condition of the roads, there are 13 RTs inadequate. b) The condition of clean water infrastructure there are 7 inadequate RTs. c) the MCK condition that 4 RTs do not comply with the technical requirements. d) the state of the waste is 5 RTs which are not maintained. e) inadequate drainage conditions 8 RTs. 3. Social characteristics: a) the population density is 3 RTs with level. b) income level there are 10 low-income RTs households. Then obtained soft slum levels in 26 RTs and 10 RTs with a moderate level.